THE IMPLEMENTATION OF AUSTRALIAâ€™S MARITIME DEFENSE STRATEGY IN RESPONSE TO CHINAâ€™S MILITARY MODERNIZATION IN THE INDO-PACIFIC REGION (2013-2016) - Banyu Perwita; Isti Marta Sukma (Kajian Asia Pasifik, 2018)
Along with economic development of a country, the sphere of the national interests are automatically cultivates. China, with the rapid economy development, has been undergoing military modernization in order to protect their national interests better. Indo-Pacific region as one of the most crucial region in the world, dynamically, has been evolved into major powers countriesâ€™ favorite region particularly the maritime sector. Australia, which located inside the Indo-Pacific region as well as the one that puts most of the national interests in the region, has been aware that Chinaâ€™s military modernization can not be fully perceived as â€œpeaceful riseâ€ due to uncertain future circumstances. The purpose of this research is to examine the maritime defense strategy response of Australia regarding Chinaâ€™s military modernization in Indo-Pacific region. This research provides further explanation regarding Australiaâ€™s standpoint in Indo-Pacific region, Chinaâ€™s military modernization and the sphere of influence in Indo-Pacific, and most importantlyâ€”the analysis of Australiaâ€™s implementation of the maritime defense strategy in responding Chinaâ€™s military modernization in the region. Keywords: Maritime strategy, Chinaâ€™s Military Modernization, Indo-Pacific, Defense Strategy, National Interests, Naval Power. Abstrak Seiring dengan perkembangan ekonomi suatu negara, bidang kepentingan nasional berkembang secara otomatis. China, dengan perkembangan ekonomi yang pesat, telah menjalani modernisasi militer untuk melindungi kepentingan nasional mereka dengan lebih baik. Kawasan Indo-Pasifik sebagai salah satu wilayah paling krusial di dunia, secara dinamis, telah berkembang menjadi favorit negara-negara besar terutama untuk sektor maritimnya. Australia, yang berada di dalam wilayah Indo-Pasifik dan juga negara yang menempatkan sebagian besar kepentingan nasional di kawasan ini, telah menyadari bahwa modernisasi militer China tidak dapat sepenuhnya dianggap sebagai "pembangunan damai" karena keadaan masa depan yang tidak pasti. Tujuan dari penelitian ini adalah untuk menguji respons strategi pertahanan maritim Australia mengenai modernisasi militer China di wilayah Indo-Pasifik. Penelitian ini akan memberikan penjelasan lebih lanjut mengenai sudut pandang Australia di wilayah Indo-Pasifik, modernisasi militer China dan lingkungan pengaruhnya di Indo-Pasifik, dan yang paling pentingâ€”analisis implementasi strategi pertahanan maritim Australia dalam menanggapi modernisasi militer China di wilayah tersebut. Kata kunci: Maritim Australia, Modernisasi Militer China, Indo-Pasifik, Strategi Pertahanan, Minat Nasional, Kekuatan Angkatan Laut.